Miranda Prorsus: An Encyclical Letter of Pope Pius XII on Motion Pictures, TV and Radio – its Impact on the Catholic Church Media in Zambia Today - Kibombwe, Freeborn (Annales Missiologici Posnanienses, 2020)
This article reflects on the sixty years marking the anniversary of the encyclical letter Miranda Prorsus by Pope Pius XII. Miranda Prorsus was the first document written in 1957 by the Church to refl ect on the three important means of communication: Motion Pictures (Film), Television (TV) and Radio. It highlighted the importance of these “remarkable technical inventions” to aid humanity in as far as development and understanding the media was concerned. Each of these three instruments of communication is examined in both the strengths and weaknesses they carry, but much more, how they can play a role in advancing humanity in the area of morality and truth telling. The article tries to use some of the important highlights in the context of Zambia my country that has embraced these means of communication with radio stations set up by the respective Bishops and a Television soon to be launched by the Zambia Conference of Catholic Bishops (ZCCB). In retrospect the article tries to show how these means and technical inventions can become handy in as far as the evangelization is concerned.